A Narrative Review of Neuroimaging Studies in Acupuncture for Migraine. (10th November 2021) - Ma, Peihong; Dong, Xiaohui; Qu, Yuzhu; He, Zhaoxuan; Yin, Tao; Cheng, Shirui; Tian, Zilei; Teng, Yuke; Xie, Kunnan; Sun, Ruirui; Yu, Siyi; Zeng, Fang
Abstract : Acupuncture has been widely used as an alternative and complementary therapy for migraine. With the development of neuroimaging techniques, the central mechanism of acupuncture for migraine has gained increasing attention. This review aimed to analyze the study design and main findings of neuroimaging studies of acupuncture for migraine to provide the reference for future research. The original studies were collected and screened in three English databases (PubMed, Embase, and Cochrane Library) and four Chinese databases (Chinese National Knowledge Infrastructure, Chinese Biomedical Literature database, the Chongqing VIP database, and Wanfang database). As a result, a total of 28 articles were included. Functional magnetic resonance imaging was the most used neuroimaging technique to explore the cerebral activities of acupuncture for migraine. This review manifested that acupuncture could elicit cerebral responses on patients with migraine, different from sham acupuncture. The results indicated that the pain systems, including the medial pain pathway, lateral pain pathway, and descending pain modulatory system, participated in the modulation of the cerebral activities of migraine by acupuncture.